2021
DOI: 10.1002/hep4.1770
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Mast Cells in Tumor Predicts Recurrence of Hepatocellular Carcinoma After Liver Transplantation

Abstract: Tumor‐infiltrating immune cells are relevant prognostic and immunotherapeutic targets in hepatocellular carcinoma (HCC). Mast cells play a key role in allergic response but may also be involved in anticancer immunity. Digital morphometric analysis of patient tissue sections has become increasingly available for clinical routine and provides unbiased quantitative data. Here, we apply morphometric analysis of mast cells to retrospectively evaluate their relevance for HCC recurrence in patients after orthotopic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Patients lacking intratumoral mast cells showed larger tumors and higher recurrence rates, indicating the potential roles of mast cells in anti-cancer immunity. 99 Further studies are required to elucidate the roles of mast cells in the pathophysiology of liver cancer, which is important to develop novel therapeutic strategies targeting mast cells.…”
Section: Mast Cellsmentioning
confidence: 99%
“…Patients lacking intratumoral mast cells showed larger tumors and higher recurrence rates, indicating the potential roles of mast cells in anti-cancer immunity. 99 Further studies are required to elucidate the roles of mast cells in the pathophysiology of liver cancer, which is important to develop novel therapeutic strategies targeting mast cells.…”
Section: Mast Cellsmentioning
confidence: 99%
“…Previous studies have revealed that mast cells had proor anti-tumorigenic roles depending on the tumor types, the stage, and localization within the tumor. Activated mast cells have been shown to be associated with poor prognosis in thyroid cancer (38), gastric cancer (39), hepatic cellular carcinoma (40), and colorectal cancer (41). Mast cell density is increased in gastric cancer, and correlated with angiogenesis, the number of metastatic lymph nodes, and patient survival (42).…”
Section: Discussionmentioning
confidence: 99%
“…A reduced number of interferonproducing NK cells has been linked to advanced stages of HCC, suggesting their potential role in predicting disease prognosis (Lee et al, 2021). Furthermore, clinical observations have revealed a negative correlation between the presence of tryptase-positive mast cells and overall survival in HCC, indicating that mast cells could serve as a potential prognostic indicator for unfavorable clinical outcomes (Wang et al, 2018;Rohr-Udilova et al, 2021). Given these connections, it is crucial to thoroughly examine the function of immune cells in HCC pathology.…”
Section: Id Compound Structure 10 Deguelinmentioning
confidence: 99%